Maternal spawning experience and thermal effects on offspring viability of chub mackerel and their influence on reproductive success - Yoneda, Michio; Kitano, Hajime; Nyuji, Mitsuo; Nakamura, Masahiro; Takahashi, Masanori; Kawabata, Atsushi; Matsuyama, Michiya; Shimizu, Akio; Tsuzaki, Tatsuo; Togashi, Hiroyuki; Kamimura, Yasuhiro (Frontiers in Marine Science, 2022)
Maternal effects on offspring viability significantly contribute to the productivity and resilience of exploited marine fish populations. The temporal trend of biomass of chub mackerel (Scomber japonicus) in the western North Pacific showed cyclic fluctuation patterns, but it has been rapidly increasing since 2011. Although there are several assumptions regarding the mechanisms of the population dynamics of this species in these waters, there is a contradiction in the effects of thermal environmental conditions on recruitment success. We explored the effects of maternal age and/or previous spawning experience on egg and offspring traits of captive chub mackerel in response to thermal conditions. Moreover, from the relationship between the growth rate and temperature experienced by captive fish, the experienced temperatures of wild specimens were assessed. The sizes of eggs spawned from females aged 1–3 years were negatively correlated with temperature, but the effects of maternal age on egg size and nutrition were significant with larger and nutrient-rich eggs spawned from 2- or 3-year-old females (repeat spawners) than those from 1-year-old females (first-time spawners) at a given temperature. Such temperature- and maternal-age-dependent egg traits reflected the standard length of first-feeding larvae. The effects of maternal age on the starvation tolerance of larvae after hatching and body sizes of first-feeding larvae were also evident in larvae derived from 3-year-old females showing longer starvation tolerance and larger body heights than those from 1-year-old females. Further, larvae derived from 3-year-old females grew significantly faster than those from 1-year-old females at the tested temperatures. The process of ontogenetic development and growth rate of captive specimens until age 25 days were positively correlated with temperature. Meanwhile, the estimated temperatures experienced by wild specimens until age 25 days ranged from 18.0 to 20.3°C. These findings suggested that there were opposing thermal responses between maternal and offspring traits of chub mackerel, but the temperatures experienced by the main recruit fish may be restricted within the range of temperatures available for spawning. We discuss the mechanisms of reproductive success of this species in accordance with the maternal spawning experience and thermal effects on life history traits.